2011
DOI: 10.1002/dev.20580
|View full text |Cite
|
Sign up to set email alerts
|

Children's noncompliance during saliva collection predicts measures of salivary cortisol

Abstract: Salivary cortisol has been useful for evaluating children's physiological responses to stress and for identifying factors that predict their magnitude and duration. However, results have been somewhat equivocal across studies, and this has motivated researchers to identify sources of variance and error. Here, we examined the prevalence of preschoolers' noncompliance during saliva collection and aimed to learn about noncompliant children in terms of their hypothalamus-pituitary-adrenal function, behavior in oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Furthermore, our data suggest that PD and OS may not be used interchangeably. Our data extend previous findings showing that saliva collection method can affect the salivary concentrations of stress and non-allergic inflammatory markers 69 .…”
supporting
confidence: 90%
“…Furthermore, our data suggest that PD and OS may not be used interchangeably. Our data extend previous findings showing that saliva collection method can affect the salivary concentrations of stress and non-allergic inflammatory markers 69 .…”
supporting
confidence: 90%
“…Recent research has found that children’s noncompliance with saliva sampling relates to both cortisol levels and adjustment outcomes, suggesting that missing cortisol values may occur non-randomly (Kaitz, Sabato, Shalev, Ebstein, & Mankuta, 2012). Multiple imputation is the recommended approach for preventing biased results when data are not missing completely at random (Graham, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Urine collections also allow for more frequent collection than repeated venepuncture would be tolerated [ 26 ]. Salivary samples are potentially easier to collect, but blood contamination and influence of flow-rate on measurements seriously limits validity and accuracy and these may be subject to non-compliance by children [ 27 ].…”
Section: Discussionmentioning
confidence: 99%